Features of organising sports training for men in media football - Safarov , Valekh Sabir ogly; Alifirov, A.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the characteristics of the content of sports training components for men in media football. Methods and structure of the study. An analysis of scientific and methodological literature on the research problem was conducted, and various aspects of the media football club's activities in the sports segment were studied. The pedagogical experiment and observations were conducted from February to November 2024 at the Russian amateur media football club Amkal in Moscow. The experimental groups consisted of 14 people, aged 21-41. Training plans, athletes' diaries and training loads during the preparatory period were also studied. Model characteristics of loads in micro- and mesocycles of the preparatory and competitive periods were introduced into the footballers' training programme. Results and conclusions. The effectiveness of the training system, based on the Russian amateur media football club Amkal, was due to the creation of a set of interconnected and organised training factors, as well as maintaining the players' level of fitness during the competitive period.